Development of Cu Nanoparticle Loaded Oil Palm Fibre Reinforced Nanocomposite - Ridzuan, Ramli; Khan, Maksudur R.; Chowdhury, Najmul Kabir; Beg, M. D. H.; Rohaya, Mohamed Halim; Astimar, Abdul Aziz; Zawawi, Ibrahim; Nahrul Hayawin, Zainal (Scientific Research, 2013)
Functionalized copper nanoparticles (FCuNPs) have been synthesized by chemical reduction method and polyvinyl al- cohol (PVA) performed as a stabilizer in that medium. Analysis observed that the average size of the synthesized FCuNPs was 3.5 nm. The obtained FCuNPs were loaded in the oil palm empty fruit bunch (EFB) natural fibre. Before the loading of FCuNPs in EFB fibres, the surface of the fibres is tailored by the cationic agent CHPTAC since they have a natural tendency to exhibit negatively charged surface owing to the presence of large amount of hydroxyl groups. Thereafter, different types of composite were developed and their properties were studied. The composites were devel- oped by using the untreated empty fruit bunch (UEFB) fibres and FCuNPs loaded EFB (NP-CAEFB) fibres with com- mercially available unsaturated polyester resin (UPER). The synthesized composites were characterized through FTIR, FESEM, XRD, DSC, tensile strength tests, etc. The obtained biodegradation results indicated that significant weight loss was not observed for neat PER and PER/FNP-CAEFB nanocomposite, whereas, the UEFB/VUPER composite showed ca. 21.4% weight loss at 90 days, which was considered rationally due to the preferential degradation of the fibre.